Rola Komisji Bioetycznej w ocenie rzetelności eksperymentów medycznych na ludziach = The role of bioethics commissions in evaluating the reliability of medical experiments on people - Ślęczek-Czakon, Danuta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
There are 69 bioethics commissions in Poland that give their opinions on scienti?c research (experiments) on people. After explaining the necessary terminological issues regarding the classi?cation of scienti?c research in medicine, the legal and ethical bases of the commissions` activity, and the principles of assessing and controlling medical research, the author addresses the scope of independence and integrity of the bioethics commission. In the ?nal part of the article, the author discusses the objections raised against bioethics commissions - especially, those concerning their independence, objectivity and reliability in the assessment of research proposals.
Keywords: komisja bioetyczna; eksperymenty medyczne na ludziach; etyka badań naukowych w medycynie; bioethics commission; medical experiments on people; ethics of scienti?c research in medicine